Synthesis of polysubstituted azetidines via cascade trifluoromethylation/cyclization of N-allyl ynamides. Issue 16 (17th June 2021) - Zhou, Genlai; Su, Jingwen; Shang, Tianbo; Wang, Xiaojuan; Bai, Yihui; Yuan, Zheliang; Zhu, Gangguo
Abstract : A cascade trifluoromethylation/cyclization of N -allyl sulfonylynamides is developed, providing a direct access to azetidine-fused tricyclic compounds at room temperature. Abstract : Traditional methods for the transformation of N -allyl ynamides rely on the formation of a ketenimine intermediate or its equivalent, while novel reaction modes remain to be developed. Herein, a cascade trifluoromethylation/cyclization of N -allyl sulfonylynamides is realized, which provides a facile access to azetidine-fused tricyclic compounds under very mild reaction conditions. It represents a rare example of 4- exo-dig radical cyclization, thus opening up a new opportunity for constructing synthetically attractive azetidines from the readily available N -allyl ynamides.